FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN POS PEMBINAAN TERPADU (POSBINDU) PENYAKIT TIDAK MENULAR DI KABUPATEN TULANG BAWANG BARAT TAHUN 2020 - Maryati, Maryati; Budiati, Endang; Noviansyah, Noviansyah (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Background: The low visit of Posbindu PTM shows the low awareness of community about the importance of Posbindu PTM. It means there is a gap of Posbindu PTM services with the response of the community. Purpose: to know the factors related to Posbindu PTM visit in Tulang Bawang Barat Regency in 2020. Methods: Type of research is quantitative with cross sectional approach. The population is the target of Posbindu (age>15 years) and adopted 439 samples. Data analysis using univariate analysis, bivariate (chi square) multivariate (multiple logistic regression). Results: there is a relationship between knowledge (p=0.000), attitude (p=0.000), education (p=0,000), income (p=0.004), accessibility (p=0.007) and support of health workers (p=0.000) with Posbindu PTM visit. Knowledge is the dominant factor related to Posbindu PTM visits (p = 0.000).Conclusion: Determinant of Posbindu PTM Visit are knowledge, attitude, education, income, accessibility and support of health workers with Posbindu PTM visit, that’s why this research perfecting Standard of operational procedure and disseminating information on hypertonic infusion fluid and monitoring it regularly and continuously.